The relationship between career strategies and career success - Tan, Fee Yean; Yahya, Khulida Kirana (Universiti Utara Malaysia, 2008)
This study examined the relationship between career strategies and career success. The three dimensions that measured career strategies were enhancing promotability, strengthening external contacts, and improving image with superiors. Meanwhile, the dimension that measured career success was subjective career success. Data were gathered through questionnaires administered to employees at a manufacturing organisation (n=185). Correlation and regression analyses were used to examine the relationship between career strategies and career success. The results indicated that there were no relationship between career strategies and career success. Only two of the career strategy dimensions were positively correlated with career success, namely strengthening external contacts and improving image with superiors. The multi-regression results suggested that improving image with superiors was the most important factor in influencing individual’s career success. The findings were discussed and recommendations for future research were also addressed.